PERAN LAYANAN KONSELING INDIVIDU MELALUI TEKNIK ROLE-PLAY UNTUK MENGATASI SISWA YANG MEMILIKI MASALAH SOSIAL DEFISIT DI MAN 1 SURAKARTA TAHUN PELAJARAN 2023/2024 - Annissa Putri; Hera Heru Sri Suryanti; Eko Adi Putro (JIP: Jurnal Ilmu Pendidikan, 2024)
The purpose of this study is to determine the Role of Individual Counseling Services with Role-Play Techniques to Overcome Social Deficits at Man 1 Surakarta in 2023/2024. This study is a qualitative descriptive study. In this study, the subject taken was one student with the initials X, namely by taking the object of one student who has a social deficit problem. Data collection techniques using interviews conducted with the guidance and counseling teacher, then observations conducted by researchers and guidance and counseling teachers and finally documentation. Based on data analysis, data was obtained from students with the initials X, students who have problems at school basically need guidance and counseling. Based on the results of the data that has been collected and carried out by researchers through observation, interviews. Then the analysis process was carried out between research information using field notes and documentation, then the researcher presented conclusions about individual counseling services with role play techniques in overcoming students who have social deficit problems. The implementation of individual counseling services is carried out if there are personal problems with students that may interfere with the effectiveness of students in learning or in socializing with their surroundings. Such as the learning process because he feels unable to express his opinion or often feels that what he does is always wrong or feels excessive shame. This is where individual counseling is used to find out what causes students to experience social deficit problems, by knowing the cause, the guidance and counseling teacher will try to help, build self-confidence, provide motivation, suggest activities that may be enjoyed and try in such a way to help students overcome social deficit problems in themselves.